-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b
b^2 - 7b + 12 = b^2 - 4b - 3b + 12 = b(b -4) -3(b - 4) = (b - 3)(b - 4)
3b + 2a = 2 and -2 + a = 8 -2 + a = 8 can be rearranged to show a = 8 + 2 = 10 (Effectively 2 has been added to both sides.) As a = 10, the value for a can now be substituted in the equation 3b + 2a = 2 3b + 2x10 = 2 : 3b + 20 = 2 this can be rearranged to show 3b = 2 - 20 = -18 and dividing both sides by 3 gives b = -6.
b2 - 7b - 6b = -4(-4)2 - 7(-4) - 6 = 16 +28 - 6 = 38
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3
3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7
3b -2 =7 b+4
If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.
Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5
2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================
If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified
First lets set up the equation.12 - 7b + 10b = 18.Now lets combine all like terms on the left hand side.12 - 7b + 10b = 1812 + 3b = 18Now lets combine all like terms using the like terms on the left side and on the right side.12 + 3b = 18-12 -123b = 6Now lets divided (since the 3 is being multiplied to the b).3b/3 = 6/3So your final answer is:b = 2
-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b
3b + 6 = 12 3b = 6 b = 2
b^2 - 7b + 12 = b^2 - 4b - 3b + 12 = b(b -4) -3(b - 4) = (b - 3)(b - 4)
N=3.1
3b + 2a = 2 and -2 + a = 8 -2 + a = 8 can be rearranged to show a = 8 + 2 = 10 (Effectively 2 has been added to both sides.) As a = 10, the value for a can now be substituted in the equation 3b + 2a = 2 3b + 2x10 = 2 : 3b + 20 = 2 this can be rearranged to show 3b = 2 - 20 = -18 and dividing both sides by 3 gives b = -6.